Measurement Theory - Krebs, David E. (Physical therapy, 1987)
The usefulness and truthfulness of assessments, whether performed in the clinic on one patient or in the research laboratory on many subjects, depends on valid measurements. Measurement theory is the thought process and interrelated body of knowledge that form the basis of valid measurements. Translation of measurement theory to behaviors helps to ensure the integrity and relevancy of tests and the data that result from them. In the final analysis, useful and truthful data depend for their existence on scalable and detectable events being translated into pertinent, valid, and reliable measurements. The rules by which numbers are assigned to events form the basis of measurements theory.